Discursive Construction of Interfaith Coexistence In Indonesia and Pakistan: Ideology, Tradition, and Practices of Tolerance - M Thoriqul Huda; Moiza Rasikh (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2026)
Indonesia and Pakistan are two countries with different ideological foundations. Indonesia is based on Pancasila as the state ideology that accommodates religious diversity, while Pakistan is built on the identity of Islam as the state religion. These ideological differences influence each country's policies in regulating interfaith relations, including guaranteeing religious freedom and protecting minority groups. However, various forms of violence and conflict based on religion are still found in both countries. This study aims to analyze the strategies implemented by Indonesia and Pakistan in building interfaith coexistence and identify various practices that have been carried out to strengthen tolerance and social harmony. Unlike previous studies that primarily examine interfaith relations within a single national context, this study comparatively investigates how different ideological foundations shape strategies of interreligious coexistence in two Muslim-majority countries. This study employs a qualitative comparative approach based on policy documents, previous empirical studies, and reports concerning interfaith relations in Indonesia and Pakistan. The results show that success in building interfaith harmony is not solely determined by state ideology, but rather by the ability of the state and society to integrate religious values, local culture, and dialogue mechanisms into social life. Indonesia and Pakistan demonstrate that tolerance can develop through different pathways according to their respective social, cultural, and political contexts. Nevertheless, both share the same goal: to create a peaceful, inclusive society that respects differences and allows for harmonious coexistence within this diversity. Despite their different ideological foundations, both countries have developed various institutional and societal mechanisms aimed at managing religious diversity and promoting peaceful coexistence.